The Role of Learning Styles in Mediating the Effects of Resilience, Learning Climate, and Self-Efficacy on Vocational Students’ Mathematical Reasoning - M. Iqbal Maulana Halisna; Sunismi Sunismi; Anies Fuady (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This study aims to analyze the influence of mathematical resilience, learning climate, and self-efficacy on the mathematical reasoning ability of vocational school students, considering learning style as a mediator and independent variable. Using a quantitative approach with an explanatory-predictive design, data were collected from 200 students at two vocational schools in Dampit East Java and analyzed with PLS-SEM. The results showed that out of the ten hypotheses tested (H1–H10), six hypotheses were significantly accepted.